What might a decolonial perspective on child protection look like? Lessons from Kenya. (August 2022) - Nyamu, Irene K; Wamahiu, Sheila P
Using decolonial perspective, this paper critically examines how certain child protection interventions in Kenya might increase childhood vulnerabilities among children from poor social backgrounds who are disproportionately represented in the justice system. Findings point to ambivalent child protection practices as a result of entrenched colonial legacies which criminalises juvenile 'delinquents', relying heavily on judicialisation while limiting social welfare investments. The study suggests alternative approaches to better child protection services that take into account southern-centric childcare practices and knowledge.